Time - Energy Uncertainty and Electronic Correlation in H+ - Graphite Collisions - Bonetto, Fernando Jose (2015)
The formation of negative ions in the scattering of protons by a highly oriented pyrolytic graphite (HOPG) surface is theoretically and experimentally analyzed for a large scattering angle and compared with previous results obtained in the same system but for a forward scattering geometry. These experiments were motivated by the fact that the interaction of a hydrogen atom with a surface is the prototype system for studying the intra-atomic Coulomb repulsion in an s-like valence orbital localized in the atom. We tried to answer the open questions related to the electronic correlation effects and the influence of the detailed surface band structure by using appropriate theoretical models. The comparison with the experiment of theoretical results obtained by using different limit approximations of the electronic repulsion in the atomic state shows the expected validity ranges according to the ion velocity. However, the most remarkable conclusion obtained from this comparison is the nonvalidity of an adiabatic picture of the energy levels shifted by the interactions with the surface atoms, when the energy uncertainty introduced by the ion velocity becomes of the order of the electronic repulsion in the hydrogen ground state.